2010
DOI: 10.1002/uog.7545
|View full text |Cite
|
Sign up to set email alerts
|

Continuous independent quality control for fetal ultrasound biometry provided by the cumulative summation technique

Abstract: Objective To apply the cumulative summation (CUSUM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…In the field of obstetrics and gynecology, studies using the CUSUM method have been limited to assessing proficiency in procedures such as embryo transfer for in vitro fertilization [35], certain diagnostic ultrasound procedures [36,37], and fetoscopic laser ablation [38]. To our knowledge, this is the first report to evaluate the learning curve of robot-assisted surgery in gynecology using the CUSUM method.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of obstetrics and gynecology, studies using the CUSUM method have been limited to assessing proficiency in procedures such as embryo transfer for in vitro fertilization [35], certain diagnostic ultrasound procedures [36,37], and fetoscopic laser ablation [38]. To our knowledge, this is the first report to evaluate the learning curve of robot-assisted surgery in gynecology using the CUSUM method.…”
Section: Discussionmentioning
confidence: 99%
“…The individual learning curves of the examiners were analyzed by the cumulative summation (CUSUM) technique . We assessed learning CUSUM curves for each examiner, plotting a cumulative score based on the absolute percentage error.…”
Section: Methodsmentioning
confidence: 99%
“…Unacceptable performance could be declared if it crossed 2 consecutive boundary lines from below. At the beginning of the process, the starting point 0 could be counted as the first intersection …”
Section: Methodsmentioning
confidence: 99%
“…As reported previously, the level of acceptable type I error was at α = 0.05 (probability of claiming that the trainee is competent while they are not) and type II error at β = 0.20 (probability of rejecting the fact that the trainee has reached their competency). Based on previously published data, our sample weight X = 0 (success) was calculated at 0.0080043, sample weight X = 1 (failure) at -1.38629, the Average Run Length ARL 0 = 40 and the decision interval h = 2.5 [5][6][7][8][9] …”
Section: Acceptable and Unacceptable Failure Ratesmentioning
confidence: 99%
“…Numerous authors have emphasized the discrepancies regarding the number of the surgical procedures one need to perform to be deemed competent [1]. Cumulative sum control charts (CUSUM) are widely applied for industrial quality control, and have been found effective for measuring and monitoring healthcare outcomes [2][3][4][5]. A new statistical tool, the cumulative summation test for learning curve (LC-CUSUM), was developed to address that issue and to assist in assessment of the learning curve (LC) and competency of a given trainee [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%